Community Guidelines for Household Waste Management - Riyasarn , Yoottapong; Chaosangrat , Chaowarit; Sangthongluan , Chatchawal (Journal for Developing the Social and Community, 2023)
The innovation of integrated household waste management is a new working method or waste management mode. Different from the previous household waste management, this is the same. There is a garbage can in the garbage truck of the community and government agencies to collect and impress. The impact on the community environment. Therefore, the purpose of this study is to develop a new and systematic waste management innovation. Through the use of traditional household waste management methods, the problem of household waste has not ended from Thai society. Household waste management innovation: the removal of garbage in the community. Government agencies must provide it to people in the community. Participation in household waste management from policy formulation In this study, knowledge preparation and participation in practice. In the budget allocation of waste management, such as the purchase of smoke-free waste, each community has its own waste management. In addition, the home decoration manual, the promotion activities of home decoration, and the reception institution. waste management Keywords : 1. Innovation 2. Waste management 3. Integration